Entrepreneurial orientation of Small Medium Entreprise (SMEs) in the Malaysian information communication technology (ICT) sector - Omar, Rosmini (Academic Journals, 2011)
This paper describes the unique entrepreneurial orientation of Malaysian entrepreneurs in the information communication technology (ICT) industry as they led companies in an environment that reflected entrepreneurial diversity, complicated markets and a surviving economy. The empirical work combined survey and case studies of 24 small and medium enterprises (SME), some of which have steered their organizations from humble start-ups to professional ventures. Results show that the successful entrepreneurs committed their strategic intentions to become global archetypal capitalists while simultaneously co-exist (despite their heterogeneous backgrounds) to serve the needs of an emerging economy. Practically, they reflect eight entrepreneurial orientations, clustered into three distinct competencies: Self-intangible, operational and global.